2020
DOI: 10.2147/ijn.s242359
|View full text |Cite
|
Sign up to set email alerts
|

<p>Magnetically Directed Enzyme/Prodrug Prostate Cancer Therapy Based on β-Glucosidase/Amygdalin</p>

Abstract: Background: β-Glucosidase (β-Glu) can activate amygdalin to kill prostate cancer cells, but the poor specificity of this killing effect may cause severe general toxicity in vivo, limiting the practical clinical application of this approach. Materials and Methods: In this study, starch-coated magnetic nanoparticles (MNPs) were successively conjugated with β-Glu and polyethylene glycol (PEG) by chemical coupling methods. Cell experiments were used to confirm the effects of immobilized β-Glu on amygdalin-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…The first objectives of this research was to verify the concept that amygdalin triggers growth inhibition in human prostate cancer cell line PC3 cells in vivo and to analyze its metabolic enzymes rhodanese and betaglucosidase as a potential adjunct to the existing prostate cancer therapy regimen ( Figure 5 ). In in vivo, amygdalin injection reduced tumour development in PC3 cells through an apoptotic mechanism induced by betaglucosidase activation [ 32 , 33 ]. According to specific research, cancer cells have a high concentration of betaglucosidase, which may be used to break down amygdalin and produce cyanide, which is harmful to cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first objectives of this research was to verify the concept that amygdalin triggers growth inhibition in human prostate cancer cell line PC3 cells in vivo and to analyze its metabolic enzymes rhodanese and betaglucosidase as a potential adjunct to the existing prostate cancer therapy regimen ( Figure 5 ). In in vivo, amygdalin injection reduced tumour development in PC3 cells through an apoptotic mechanism induced by betaglucosidase activation [ 32 , 33 ]. According to specific research, cancer cells have a high concentration of betaglucosidase, which may be used to break down amygdalin and produce cyanide, which is harmful to cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, malignant cells lack RHD, and so the creation of HCN is stored in these cells [ 18 , 28 – 30 ]. AMD may have a therapeutic impact on prostate cancer by inhibiting the viability of PC3 cells in vitro [ 17 , 31 , 32 ]. Additionally, no report of the same outcomes in vivo has been recorded.…”
Section: Introductionmentioning
confidence: 99%
“…Amygdalin possesses therapeutic effect against atherosclerosis [9], in the management of autoimmune hepatitis [54], and anti-tumor effects against various cell lines [13,16,25,35,41,[55][56][57]. This phytocompound can affect the cell cycle of cancer cells, reduce cell cycle activators, especially cyclin B, cdk1, E-cadherin, and N-cadherin and activate multiple cellular pathways, inhibit the Akt-mTOR signaling pathway thereby inhibiting the proliferation of cancer cells [45,56,58].…”
Section: Physiological and Therapeutic Rolesmentioning
confidence: 99%
“…This inspires further in vivo analysis of the prepared amygdalin-loaded ACNPs on cancer tumor models. Recently, Zhou et al [42] showed that by chemical coupling methods, starch-coated magneticiinanoparticles (MNPs) were successively conjugated with β-glucosidase (β-Glu) iand polyethylene glycol (PEG). Consequently, amygdalinmediatediimmobilized β-Glu activatediprostate cancer cell death.…”
Section: Microencapsulation and Bioavailabilitymentioning
confidence: 99%